DNA-Methylation: Master or Slave of Neural Fate Decisions? - Stricker, Stefan H.; Götz, Magdalena (Frontiers in Neuroscience, 2018)
The pristine formation of complex organs depends on sharp temporal and spatial control of gene expression. Therefore, epigenetic mechanisms have been frequently attributed a central role in controlling cell fate determination. A prime example for this is the first discovered and still most studied epigenetic mark, DNA methylation, and the development of the most complex mammalian organ, the brain. Recently, the field of epigenetics has advanced significantly: new DNA modifications were discovered, epigenomic profiling became widely accessible, and methods for targeted epigenomic manipulation have been developed. Thus, it is time to challenge established models of epigenetic gene regulation. Here, we review the current state of knowledge about DNA modifications, their epigenomic distribution, and their regulatory role. We will summarize the evidence suggesting they possess crucial roles in neurogenesis and discuss whether this likely includes lineage choice regulation or rather effects on differentiation. Finally, we will attempt an outlook on how questions, which remain unresolved, could be answered soon.